Long-term population status of two harvested intertidal grazers (Patella aspera and Patella candei), before (1996–2006) and after (2007–2017) the implementation of management measures - Sousa, Ricardo; Vasconcelos, Joana; Henriques, Paulo; Pinto, Ana Rita; Delgado, João; Riera, Rodrigo (Journal of sea research, 2019)
Intertidal limpets are subject to harvesting pressure in regions, e.g. oceanic islands, where marine organisms are a more accessible source of protein. These molluscs are very sensitive to human exploitation which often results on a decrease of their densities and an over-representation of immature individuals, because of the loss of large-sized reproductive specimens. Two species of exploited limpets (Patella aspera and Patella candei) were assessed throughout 21 years, before (1996–2006) and after (2007–2017) the implementation of conservation measures for their sustainable management in Madeira (North-eastern Atlantic Ocean). Different levels of anthropogenic pressure were also taken in account in this comparative study: (i) proximity to coastal settlements (“Near” vs. “Far”) and (ii) accessibility to the coast (North vs. South), that may be considered surrogates of harvesting pressure on the intertidal of Madeira. The present results showed that the stocks of P. aspera and P. candei are slightly recovered after regulatory measures entered into force, with an increase of mean shell length and dominance of reproductive individuals (>40 mm). P. aspera populations showed a clearer effect mainly due to the higher exploitation rate relative to P. candei. Conservation measures prompted a positive effect on both exploited limpet species, but further assessment studies are necessary to address the evolution of stocks over time. •Populations of P. aspera and P. candei were assessed throughout 21 years in NE Atlantic.•Impact of harvesting effort on the stocks of P. aspera and P. candei was evaluated.•Effect of proximity and accessibility on the stocks was analysed.•Stocks of limpets are slightly recovered after regulatory measures entered into force.•Further assessment studies are warranted to address the evolution of stocks over time.